Reproductive performance of Santa Ines ewes during dry and rainy seasons in eastern Amazon - Moura, A. C. B.; Teixeira, P. P. M.; Coutinho, L. N. [UNESP]; Paz, C. C.; Santos, V. J. C. [UNESP]; Soares, F. N.; Oliveira, M. E. F. [UNESP]; Vicente, W. R. R. [UNESP]; Araujo, A. A.; Rodrigues, L. F. S. (Brazilian Coll Animal Reproduction, 2014)
The aim of this study was to evaluate the reproductive performance of ewes during the dry and wet months in northern Brazil. The females were divided into two groups: reproduced during the dry season and lambing in the rainy season (Group A, n = 38), and the opposite with the other group (Group B, n = 55). There was no difference (P > 0.05) for expression of estrus (86.8 and 98.3%), pregnancy rate (86.8 and 90.9%), lambing (76.3 and 83.6%), abortion (9 and 7.4%), fecundity (86.8 and 96.3%), birth (103.4 and 110.8%) and prolificacy (113.7 and 115.2%) observed in groups A and B, respectively. However, there was a difference (P < 0.05) in lamb mortality (26.6% for group A and 49% for group B). Ewes from group A presented a higher average live weight at the end of the reproductive season and during the final third of pregnancy (P < 0.05).
Keywords: Amazonian climate; lambing season; reproductive performances; Seasonality